Impact of cardiac rehabilitation on inflammation in patients with ischaemic cardiomyopathy. (14th October 2021) - Costa, R; Frias, A; Campinas, A; Fernandes, P; Magalhaes, S; Santos, M; Torres, S
Abstract: Introduction: The benefits of cardiac rehabilitation (CR) in patients with ischaemic cardiomyopathy are well-known. However, inflammatory states have been associated to an increased risk of cardiovascular events. Purpose: Evaluate the impact of CR in the serum levels of inflammatory biomarkers and identify potential predictors of that effect. Methods: We retrospectively studied consecutive patients with ischaemic cardiomyopathy who completed a CR programme between 2011 and 2017. Patients underwent a supervised exercise training protocol, twice a week during a period of 8 to 12 weeks. Functional capacity was evaluated by metabolic equivalents assessed prior the beginning and 3 months after the programme with a symptom limited exercise treadmill test. Patients without levels of serum C-reactive protein at beginning and at the end of CR programme were excluded. Median variation of serum C-reactive protein was assessed and two groups were defined: one with levels above that and one with levels below. Results: Of 250 patients (60.3±11.1 years, 84% male), 67% were admitted after an acute myocardial infarction. Left ventricular ejection fraction ≤40% before CR was present in 32% of individuals. Median levels of serum C-reactive protein before CR were 8.8 (3.1–21.7) mg/L and median variation after CRP was a decrease of 5.1 (0.9–17.7) mg/L (p<0.001). Before CR, higher levels of serum C-reactive protein were seen in obese (15.7 [8–52.7] versus 8.8 [3.2–27.8], p=0.04) and those with higher NT-proBNP (p<0.001). Patients with decrease of >5.1mg/L of serum C-reactive protein had lower prevalence of hypertension (18% versus 30%, p=0.02), higher prevalence of obesity (16% versus 7%, p=0.03), lower levels of HDL cholesterol (38.3 [11.1] versus 43.2 [12.6], p<0.001) and higher levels of NT-proBNP (1079 [610.3–1988] versus 488 [215–777], p<0.001) at baseline. An increase of at least of 10% of functional capacity after CR was reached in 65% of patients, similar between groups. Patients with decrease of serum C-reactive protein >5.1mg/L had also higher reduction of NT-proBNP after CR comparing to baseline (491.1 [142.7–948.5] versus 162.0 [30.9–295.2], p<0.001). Conclusions: Serum levels of inflammatory biomarkers decreased after CR in patients with ischaemic cardiomyopathy. Normotension, obesity, lower HDL and higher levels of natriuretic peptides are associated to a better response. Funding Acknowledgement: Type of funding sources: None.